Joule-Thief Circuit Performance for Electricity Energy Saving of Emergency Lamps - Eka Nuryanto Budisusila; Bustanul Arifin (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
The alternative energy such as battery as power source is required as energy source failures. The other need is outdoor lighting. The electrical power source is expected to be a power saving, optimum and has long life operating. The Joule-Thief circuit is one of solution method for energy saving by using raised electromagnetic force on cored coil when there is back-current. This circuit has a transistor operated as a switch to cut voltage and current flowing along the coils. The present of current causing magnetic induction and generates energy. Experimental prototype was designed by using battery 1.5V to activate Light Emitting Diode or LED as load. The LED was connected in parallel or serial circuit configuration. The result show that the joule-thief circuit able to supply LED circuits up to 40 LEDs.